PENGERTIAN HIDUP: HUBUNGANNYA DENGAN KEBAHAGIAAN DALAM KALANGAN PEKERJA DI JOHOR BAHRU - Abdol Raop, Noraini; Abdul Kadir, Nor Ba’yah; Md. Radzali, Sa’adah (Jurnal 'Ulwan, 2023)
The meaning in life and happiness is one of the variables in the field of positive psychology that is often the focus of psychological researchers' studies. This study aims to see the relationship between the meaning in life and happiness amongst the workers in Johor Bahru. A total of two test tools were used, the Meaning in Life Questionnaire (MLQ) by Michael F. Steger, Patricia Frazier, Shigehiro Oishi and Matthew Kaler (2004) to measure the meaning of life and the Subjective Happiness Scale (SHS) built by Sonja Lyubomirsky (1999) to test happiness. A total of 183 employees from various employment backgrounds were involved in this study. The data analysis of this study was done using the Statistical Package for Social Science (SPSS) to obtain descriptive statistical results (mean, frequency and percentage) and inference (Pearson correlation). The findings of this study shows that the meaning of one’s life has significance relationship with employee’s happiness. This shows that workers who lead their lives meaningfully feel happy with the life that they lead despite facing various challenges both in work and in personal life. The finding shows the importance for employees to be clear in their meaning of life in order to feel happy, living life full of challenges thus preventing self from developing mental issues.